High‐Performance Delivery of a CRISPR Interference System via Lipid‐Polymer Hybrid Nanoparticles Combined with Ultrasound‐Mediated Microbubble Destruction for Tumor‐Specific Gene Repression (Adv. Healthcare Mater. 10/2023). Issue 10 (17th April 2023) - Li, Yan; Wu, Pengying; Zhu, Mingting; Liang, Meiling; Zhang, Lei; Zong, Yujin; Wan, Mingxi
Abstract : CRISPR Interference Systems The main objective of this study in article 2203082 by Yujin Zong, Mingxi Wan, and co‐workers, is to develop novel pH‐responsive lipid‐polymer hybrid nanoparticles (PLPNs) to achieve optimal CRISPRi system delivery via ultrasound‐mediated microbubble destruction (UMMD) technology, thereby inducing efficient target gene repression.